A scoping review of EFL learners’ interlanguage pragmatic development - Huaqiang Li; Zalina Mohd Kasim; Lay Hoon Ang (PLoS ONE, 2026)
Interlanguage pragmatics (ILP) development refers to how L2 learners manage actions, identities, and social relations through language in interaction. The rapid transition to multimodal, digitally mediated EFL instruction after 2020 has reshaped the conditions for ILP development. However, existing reviews largely predate this pivotal shift and offer only fragmented coverage on how these new ecologies have changed EFL learners’ prospects for ILP development and its assessment. This scoping review provides the first integrative synthesis of research on EFL learners published since 2020. Its primary goal is to consolidate dispersed evidence to identify key developmental patterns and contextual moderators. Four databases (Web of Science, Scopus, ScienceDirect, and ERIC) were searched for publications from 2021 to 2025 using predefined criteria; 56 studies met the eligibility criteria. Reporting follows PRISMA-ScR, and data were independently double-screened, coded, and analyzed thematically in ATLAS.ti 23. The analysis identified seven thematic categories ranging from core learner-internal pragmatic competencies to external pedagogical and computer-mediated contexts. Despite uneven coverage across themes and regions, findings converge on two patterns: pragmalinguistic gains often outpace sociopragmatic appropriateness and follow nonlinear trajectories, and instruction tends to outperform mere exposure when explicit form-function-context mapping, multimodal modelling, and data-driven feedback are provided. For researchers, the review highlights the need to shift toward longitudinal, interaction-sensitive designs that capture within-learner moderators and situational dynamics across broader learner groups. The distinctive contribution is a set of evidence-informed design principles that help educators and materials developers align ILP-oriented instruction and assessment with EFL learners’ varying developmental needs.